The acceptability of HIV testing among women receiving post abortion care - Lado Wani Ismail; Zahida P. Qureshi; Shadrack B. Ojwang (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2019)
Introduction: In South Sudan, few women have heard about the HIV. The prevalence of HIV infection in the country is 2.6%. Post-abortion care (PAC) accounts for over 50% of all gynaecological admissions at the Juba Teaching Hospital (JTH). HIV testing is not routinely offered as part of PAC services. Objective: To determine factors associated with acceptability of HIV testing among women receiving PAC at JTH. Methods: This was a cross-sectional study, conducted at the Gynaecological Unit of JTH. Three hundred and forty patients were interviewed using a structured questionnaire. Results: The mean age of the participants was 24.7 years with 50.5% aged <25years, 31.5% were employed, and 31.8% had no formal education. Acceptability of HIV testing was 70.9% and the prevalence of HIV was 2.7%. The most common reason for not accepting, was the belief, based on previous results, that they were HIV negative. Patients aged ≥25 years and those with primary and secondary education were twice as likely to accept HIV testing than those <25 years and those with no formal education, respectively. Employment status, religion, and marital status were not statistically associated with the acceptability of HIV testing. Patients previously tested for HIV were more likely to accept testing. Conclusion: Routine HIV testing should be integrated into PAC services with efforts to increase awareness of HIV and the importance of testing